Language politeness in the context of Jambi Malay based on gender - Pratiwi, Anggia; Yusrizal; Sri Utaminingsih (Universitas Jambi, Indonesia, 2025)
This research aimed to analyze and describe politeness in the learning process between lecturers and PSPBSI STKIP YPM Bangko students in the Jambi Malay context. This research uses a qualitative method with a case study sapproach. The data sources in this research were lecturers and class B students, semester VII, who acted as respondents. The results of the research indicate that (1) politeness in the learning process of lecturers and students is characterized by (a) direct speech acts of declarative, interrogative, and imperative, (b) first-person singular pronoun